AN ANALYSIS OF THE PRACTICE OF GOOD GOVERNANCE THROUGH IMPLEMENTATION OF THE ACCOUNTABILITY SYSTEM PERFORMANCE GOVERNMENT AGENCIES (SAKIP ) ON THE STATE SLEMAN DISTRICT - Putri Lestari Permata Kasih; Kasmadi Kasmadi; Irfan Tanjung (Jurnal Riset Manajemen Indonesia, 2020)
The purpose of this research is to find the practice of good governance through implementation of the accountability system performance government agencies ( sakip ) on the state sleman district .This research is qualitative research was conducted by the use of secondary data with the approach the study documentation .As for the study documents that are undertaken in this research is a document relating to train them the government accountability system performance such as a document guidelines for preparing sakip and lakip , and documents sakip lakip 2017-2018 year .The method of analysis descriptive used to know the extent of the level impelementasi sakip on kabupaten sleman and follow-up on the recommendations given over evaluation sakip lakip by following permenpan-rb 12 years 2015 . The outcome of research on impelementasi sakip on sleman district have been successfully, the recommendation followed by satisfactory, and could support the establishment of good governance.